Evaluation of the Treatment Efficacy of Corticosteroid Injection in Reducing the Pain Intensity in the Patients Diagnosed with the Plantar Fasciitis - Abdul Wahid, Rahim Shah, Muhammad Shakeel, Muhammad Nadeem Kashmiri (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Plantar fasciitis is an orthopedic ailment that affects athletes and non-athletes equally. The 10% of the general population attend the orthopedic surgeons with heel pain in their lifetime. The degenerative changes in plantar fasciitis worsen the conditions of patients. Objective: The study aimed to evaluate the treatment efficacy of corticosteroid injection in reducing the pain intensity in the patients clinically diagnosed with the plantar fasciitis. Study design: This descriptive study was conducted on 40 patients who attended the orthopedics department of Lady Reading Hospital Peshawar. The duration of study was one year from April 2021 to March 2022. Material and Methods: The patients who were clinically diagnosed with the plantar fasciitis and met the inclusion criteria were selected for the study. The study was approved by the ethical and review board committee of the hospital. The selected patients were administrated with the Triamcinolone injection in the heel. The visual analog scale was used to assess the outcomes. The data was collected and SPSS was used for the statistical analysis. Results: The total 40 patients were selected for the study. The mean calculated age was 42.83± 7.07. Out of 40 patients the (22) 55% were male and remaining (18) 45% were female. The mean pre injection VAS improved from 6.30±2.1 to 1.5±6 post injection. The p-value was 0.03. Conclusion: It was concluded that the single injection of corticosteroid significantly reduce the pain intensity associated with plantar fasciitis. Keywords: Triamcinolone injection and visual analog scale.